Application of CBR techniques in elderly falling risk for physiotherapist assessment and support - W. Rueangsirarak (2018)
With the aging population increasing at a faster r ate the muscular skeletal system disorder caused by falling is becoming a challenging problem to health providers. In Thailand there is lack of training of therapists to assist the elderly people following fall injuries. The need for innovative approaches to help with the care of elderly is required. This paper addresses this issue by describing a decision support system based on a case based reasoning paradigm to support the physiotherapists in their care for the elderly. © 2011 IEEE.